2023
DOI: 10.3390/pr11030676
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Chlorine Concentration in Water Distribution Systems Based on a Genetic Algorithm

Abstract: This paper proposes a methodology based on a genetic algorithms (GA) to calibrate the parameters of a chlorine decay model in a water distribution system (WDS). The proposed methodology first contemplates that a GA is implemented using historical measurements of chlorine concentration at some sensed nodes to calibrate the unknown values corresponding to both the bulk and wall reaction coefficients. Once both parameters are estimated, the optimal-fit chlorine decay model is used to predict the decay of chlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Often, the coefficients in such models depend on the loading conditions and are not practical for modeling purposes [ 57 ]. Therefore, other approaches are required [ 17 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, the coefficients in such models depend on the loading conditions and are not practical for modeling purposes [ 57 ]. Therefore, other approaches are required [ 17 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results prove that the proposed model accurately predicts free chlorine residuals (R 2 = 0.98). Gómez-Coronel et al [ 17 ] reported satisfactory results in the chlorine concentration at the input of a water distribution system simulated in EPANET, with a genetic algorithm implemented in MATLAB. The EPANET MSX software was used to model chlorine decay in Algarve’s drinking water supply systems [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gómez-Coronel et al [11] propose a two-step algorithm to calibrate the parameters of a chlorine decay model in water distribution systems (WDS) based on genetic algorithms (GA). In the first step, the GA employs historical chlorine concentration measurements at some nodes to estimate the unknown values of the bulk and wall reaction coefficients.…”
mentioning
confidence: 99%